1988
DOI: 10.1083/jcb.106.1.213
|View full text |Cite
|
Sign up to set email alerts
|

The L2/HNK-1 carbohydrate of neural cell adhesion molecules is involved in cell interactions.

Abstract: Abstract. We investigated whether the L2/HNK-1 carbohydrate epitope, expressed by two unusual glycolipids and several neural adhesion molecules, including L1, neural cell adhesion molecule, J1, and the myelin-associated glycoprotein, is involved in adhesion. Monoclonal L2 antibodies, the L2/HNK-I-reactive, sulfate-3-glucuronyl residue carrying glycolipids (L2 glycolipid) and a tetrasaccharide derived from the L2 glycolipid (L2 tetrasaccharide) were added to microexplant cultures of early postnatal mouse cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
166
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(168 citation statements)
references
References 46 publications
2
166
0
Order By: Relevance
“…The immunoaffinity-isolated AN2 antigen from brain (as well as from Oli-neu; data not shown) expresses the L2/HNK-1 carbohydrate epitope that is expressed by subpopulations of many cell adhesion molecules, including N-CAM, MAG, L1, and Tenascin-R, and has been shown to play a role in adhesion (Krüse et al, 1984;Keilhauer et al, 1985;Künemund et al, 1988). This observation supports a putative function of AN2 as an adhesion molecule.…”
Section: Carbohydrate Residues Including Glycosaminoglycan Chains Maysupporting
confidence: 63%
“…The immunoaffinity-isolated AN2 antigen from brain (as well as from Oli-neu; data not shown) expresses the L2/HNK-1 carbohydrate epitope that is expressed by subpopulations of many cell adhesion molecules, including N-CAM, MAG, L1, and Tenascin-R, and has been shown to play a role in adhesion (Krüse et al, 1984;Keilhauer et al, 1985;Künemund et al, 1988). This observation supports a putative function of AN2 as an adhesion molecule.…”
Section: Carbohydrate Residues Including Glycosaminoglycan Chains Maysupporting
confidence: 63%
“…The developmental pattern of BEN expression and the fact that it bears the HNK-1 epitope, which is thought to be implicated in adhesion phenomena in the nervous system (18), led us to speculate that BEN could be implicated in cell adhesion events such as axonal fasciculation or cell aggregation. We examined the distribution of BEN protein on the cell surface of E13 inferior olivary nucleus neurons cultured for 24 h by using confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Roles for sulfatides and SGGLs in neural cell interactions have been proposed in earlier studies. For example, it has been suggested that SGGLs and sulfatides are involved in the adhesion of dissociated cerebellar cells and outgrowth of neurites and astrocytic processes (54). SGGLs have also been shown to have effects on Schwann cell adhesion (28,55).…”
Section: Discussionmentioning
confidence: 99%